Adsorption of heavy metal with modified eggshell membrane and the in situ synthesis of Cu–Ag/modified eggshell membrane composites. Issue 9 (19th September 2018) - Xin, Yaqing; Li, Caihong; Liu, Jianing; Liu, Jinrong; Liu, Yuchen; He, Weiyan; Gao, Yanfang
Abstract : The objectives of this study were to remove heavy metals from wastewater through the biosorption method with modified biomass as an effective sorbent and to prepare metal/biomass composites with the same modified biomass as a direct template. Eggshell membrane (ESM) was selected and modified to adsorb heavy metals. Adsorption of metal ions on the modified ESM (MESM) might be attributed to electrostatic interaction, ion exchange and coordination effect with chelating ligands containing N and S on the surface of the MESM. The pH of the solution was a key factor affecting the adsorption. The Cu–Ag/MESM composites with uniform Cu–Ag NPs were prepared with MESM as matrices, and with Cu 2+ and Ag + adsorbed as metal sources. The Cu–Ag/MESM showed excellent catalytic performance in the reduction of 4-nitrophenol to 4-aminophenol in the aqueous phase. Because of the high stability of the Cu–Ag NPs supported on the macro-dimension supporter, Cu–Ag/MESM can be easily separated after the catalytic reaction and recycled.